Labor market institutions and informality in transition and Latin American countries - Hartmut Lehmann; Alexander Muravyev (Institute for the Study of Labor (IZA), 2012)
This paper analyzes, using country-level panel data from transition economies and Latin America, the impact of labor market institutions on informal economic activity. The measure of informal economic activity is taken from Schneider et al. (2010), the most comprehensive study to date. The data on institutions, which cover employment protection legislation (EPL), the tax wedge, the unemployment benefit level, unemployment benefit duration and union density, are assembled at the IZA (transition countries) and the World Bank (LAC countries). We find that a more regulated labor market (higher EPL) increases the size of the informal economy. There is also evidence that a larger tax wedge increases informality. The tax wedge elasticity of informal economy, when evaluated at the sample mean, is rather modest, around 0.1%. Our results are broadly in line with the literature, which identifies labor market regulation and the tax wedge as important drivers of informality.
Keywords: E24; J21; J42; O17; P20; 330; labor market institutions; informality; macroeconometric regressions; transition countries; Latin America; Arbeitsmarkt; Informeller Sektor; Arbeitsmarktpolitik; Arbeitnehmerschutz; Lohnsteuer; Arbeitskosten; Übergangswirtschaft; Transformationsstaaten; Lateinamerika